Internalisasi Nilai-Nilai Multikultural pada Siswa melalui Pembelajaran IPS di SMP Pangudi Luhur Domenico Savio - Rofik, Muhammad Fathur; Hermanto, Fredy (Universitas Negeri Semarang, 2021)
Pangudi Luhur Domenico Savio Junior High School is a school with a diversity of student backgrounds, from the point of view of religion, ethnicity, socio-economy, and gender / gender. This article aims to Know the process of internalizing multicultural values in students through social studies learning SMP Pangudi Luhur Domenico Savio. The results of this study found that The process of internalizing multicultural values has been carried out by the teacher, the values that are often applied by the teacher are the values of Democratization, Humanism, and Pluralism. which are inserted through various things, namely: (a) Social studies learning materials are formed based on facts and real examples in the field. (b) The learning model used is inquiry discussion with the aim that students better understand the material and can adapt to the surrounding environment. (c) The assessment system used by the teacher is not only in terms of cognitive, affective, and psychomotor, but the assessment also takes into account the opinions of other students regarding the personalities of the students concerned as evaluation materials for the future.